(untitled) (KULT_online, 2009)
Sandra Ziegler’s dissertation explores the link between the Holocaust and language. Her study of selected Holocaust literature consists of, for one, an enquiry into the identity-building interaction between writing and reading about the Holocaust for both the creating and the receiving subject. The author scrutinises Dutch and German diaries, letters, poems, reports, and memoires written during the German occupation of the Netherlands from 1940 to 1945 in the city of Amsterdam, in the transit camp Westerbork, and after the War’s end. Classifying the underlying testimonies of Jewish authors as ego documents ("I document", "I record") also enables an investigation of their explanatory power with regard to historic events and their potential use as "sources of Holocaust research" (p. 20).